Influence of pole length on metabolic and kinematic outcomes in cross-country sit-skiers - Blickensderfer, S.; Inman, M.; Jarrett, D.; Becker, J. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: Unlike able-bodied skiers, sit-skiers rely solely on poling for forward propulsion. Thus, any changes impacting poling mechanics may have a large influence on sit skier performance. While able-bodied skiers show a negative correlation between oxygen uptake and pole length [1], whether this is also true in sit-skiers remains unknown. Manipulating pole length may also influence cycle kinematics [2], a change with potential direct bearings on performance as faster sit-skiers have longer cycle lengths. Given these gaps in knowledge, the purpose of this study was to evaluate the metabolic and kinematic effects of changing pole lengths on Para Nordic sit-skiers.